Timing and volume of crystalloid and blood products in pediatric trauma: An Eastern Association for the Surgery of Trauma multicenter prospective observational study. Issue 1 (July 2020) - Polites, Stephanie F.; Moody, Suzanne; Williams, Regan F.; Kayton, Mark L.; Alberto, Emily C.; Burd, Randall S.; Schroeppel, Thomas J.; Baerg, Joanne E.; Munoz, Amanda; Rothstein, William B.; Boomer, Laura A.; Campion, Eric M.; et al.
Abstract : BACKGROUND: The purpose of this study was to determine the relationship between timing and volume of crystalloid before blood products and mortality, hypothesizing that earlier transfusion and decreased crystalloid before transfusion would be associated with improved outcomes. METHODS: A multi-institutional prospective observational study of pediatric trauma patients younger than 18 years, transported from the scene of injury with elevated age-adjusted shock index on arrival, was performed from April 2018 to September 2019. Volume and timing of prehospital, emergency department, and initial admission resuscitation were assessed including calculation of 20 ± 10 mL/kg crystalloid boluses overall and before transfusion. Multivariable Cox proportional hazards and logistic regression models identified factors associated with mortality and extended intensive care, ventilator, and hospital days. RESULTS: In 712 children at 24 trauma centers, mean age was 7.6 years, median (interquartile range) Injury Severity Score was 9 (2–20), and in-hospital mortality was 5.3% (n = 38). There were 311 patients(43.7%) who received at least one crystalloid bolus and 149 (20.9%) who received blood including 65 (9.6%) with massive transfusion activation. Half (53.3%) of patients who received greater than one crystalloid bolus required transfusion. Patients who received blood first (n = 41) had shorter median time to transfusion (19.8 vs. 78.0 minutes, p = 0.005) and less total fluid volume (50.4 vs. 86.6 mL/kg, p = 0.033) than those who received crystalloid first despite similar Injury Severity Score (median, 22 vs. 27, p = 0.40). On multivariable analysis, there was no association with mortality ( p = 0.51); however, each crystalloid bolus after the first was incrementally associated with increased odds of extended ventilator, intensive care unit, and hospital days (all p < 0.05). Longer time to transfusion was associated with extended ventilator duration (odds ratio, 1.11; p = 0.04). CONCLUSION: Resuscitation with greater than one crystalloid bolus was associated with increased need for transfusion and worse outcomes including extended duration of mechanical ventilation and hospitalization in this prospective study. These data support a crystalloid-sparing, early transfusion approach for resuscitation of injured children. LEVEL OF EVIDENCE: Therapeutic, level IV.